(untitled) (REMUNOM, 2024)
Objective: To test the toxicity of the dry crude extract of the medicinal plant Alpinia speciosa K. Shum. (colônia) against tests with Artemia salina Leach microcrustaceans, as well as analyzing their erythrocyte osmotic fragility (EFO). Methods: From maceration in absolute alcohol, filtration and evaporation of Alpinia speciosa leaves, its dry crude extract was obtained. Toxicological tests were carried out by determining erythrocyte osmotic fragility and toxicity to Artemia salina L. in the extract. The results obtained were calculated using descriptive statistical techniques. Results: Given the results obtained in toxicity tests using Artemia salina L. microcrustaceans and the FOE of the dry crude colony extract, the species demonstrated toxic characteristics. Conclusion: It was concluded that the dry crude extract of A. speciosa leaves has considerable toxicological activity. Therefore, the verification of the toxic profile of the plant species in question must be taken into consideration, given the great acceptance of the empirical use of this plant by the population.